Influences of nickel plated multi-walled carbon-nanotube on the electro-optical properties of nematic liquid crystal. (9th September 2019) - Guo, Yuqiang; Li, Wenjuan; Li, Xiaoshuai; Zhang, Hui; Ma, Hongmei; Sun, Yubao
Abstract: Some enhanced performances can be obtained by doping multi-walled carbon-nanotube (MWCNT) into self-organized nematic liquid crystal (NLC). However, the dispersion of MWCNT in NLC is very few, thus the enhancement is restricted. In this work, a nickel plated MWCNT (MWCNT@Ni) is synthesized to obtain a relatively high dispersion. The morphology, element and chemical bond differences between MWCNT and MWCNT@Ni are characterized. For MWCNT@Ni, there is a layer of coaxial nickel coated on the surface of MWCNT, which weakens the interaction energy between the adjacent MWCNTs and further results in a relatively high dispersion. Moreover, MWCNT@Ni has a more orderly arrangement in NLC compared with MWCNT. The results suggest that the dielectric anisotropy of MWCNT@Ni/NLC with mass fraction of 0.01 wt% is increased by ∼3.6%, and the saturation voltage is reduced by ∼7.3%. Besides, the rise time is decreased by ∼9.5% at 5 V and 1 kHz. These performances have been improved compared with MWCNT/NLC under the same mass fraction. The effect of mass fraction of MWCNT@Ni on rise time is further investigated. As a result, the rise time is decreased by ∼16.7% as MWCNT@Ni with mass fraction of 0.10 wt% is added into NLC. In general, the method to increase dispersion of dopant in NLC is proposed, which can serve as a reference to improve the performances of NLC composites.